Data on TOF-SIMS analysis of Cu2+, Co2+ and Cr3+ doped calcium phosphate cements - Anja Henß (Data in Brief, 2017)
This article contains data of time of flight secondary ion mass spectrometry (TOF-SIMS) analysis of brushite-forming calcium phosphate cements doped with biologically active metal ions. This data are related to the research article “Cu2+, Co2+ and Cr3+ doping of a calcium phosphate cement influences materials properties and response of human mesenchymal stromal cells” (Schamel et al., 2017) [1]. Cu2+, Co2+ and Cr3+ doped β-tricalcium phosphate precursor powders were used to prepare cement samples. The incorporation and distribution of the metal ions in the cement matrix was visualized by imaging mass spectrometry.